(untitled) (Fiep Bulletin - online, 2014)
Knowing the importance of regular reading habit, in view of the knowledge that can be acquired through its practice during academic formation, it is important an investigation about this activity as an extension of a undergrad formation in Physical Education (PE). Therefore, this research is characterized as quantitative descriptive and expresses the students reading habits in the PE course of the Federal University of Santa Catarina (UFSC). The data shows that 99,4% of the students consider that reading contributes in their professional and cultural formation, but 84,4% of them detach that their reading dedication is insufficient.